2016
DOI: 10.1021/jacs.6b00232
|View full text |Cite
|
Sign up to set email alerts
|

The Catalytic Mechanism of a Natural Diels–Alderase Revealed in Molecular Detail

Abstract: The Diels-Alder reaction, a [4 + 2] cycloaddition of a conjugated diene to a dienophile, is one of the most powerful reactions in synthetic chemistry. Biocatalysts capable of unlocking new and efficient Diels-Alder reactions would have major impact. Here we present a molecular-level description of the reaction mechanism of the spirotetronate cyclase AbyU, an enzyme shown here to be a bona fide natural Diels-Alderase. Using enzyme assays, X-ray crystal structures, and simulations of the reaction in the enzyme, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
175
0
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(207 citation statements)
references
References 28 publications
13
175
0
2
Order By: Relevance
“…Based on the structure of sporothriolide and the recently reported trienylfuranol A isolated from H. submoniticulosum, we suggested a hypothetic biosynthetic pathway of sporochartines, involving a "spiro" Diels-Alderase reaction as shown in Figure 7 (Klas et al, 2015;Byrne et al, 2016). The possibility of a nonenzymatic catalysis was excluded as reported previously (LemanLoubière et al, 2017).…”
Section: Resultssupporting
confidence: 63%
“…Based on the structure of sporothriolide and the recently reported trienylfuranol A isolated from H. submoniticulosum, we suggested a hypothetic biosynthetic pathway of sporochartines, involving a "spiro" Diels-Alderase reaction as shown in Figure 7 (Klas et al, 2015;Byrne et al, 2016). The possibility of a nonenzymatic catalysis was excluded as reported previously (LemanLoubière et al, 2017).…”
Section: Resultssupporting
confidence: 63%
“…425 They act as irreversible inhibitors of para -aminobenzoate synthase in bacterial metabolism. 425 Recent studies on the enzymes AbyA4, AbyA5 and AbyU have provided evidence for a [4+2] cyclization catalyzed by AbyU 426 (Scheme 84) on the acyclic 591 to create the indicated two ring 5,6-spirocycle 592 at the core of the 593 framework. The Aby4 and Aby5 enzymes act on the precursor tetronate ring 589 to acetylate (to give 590 ) and then eliminate the -OH group to produce the exo methylene double bond in 591 .…”
Section: Nonradical Cyclization Mechanismsmentioning
confidence: 99%
“…Further biochemical characterizations and structural studies of AbyU by Byrne et al revealed that this type of Diels-Alderase is cofactor-independent with a β-barrel scaffold. [329] The linear substrate chains are likely arranged in the active site to expedite a transannular pericyclic reaction.…”
Section: Rearrangementmentioning
confidence: 99%